Influence of Substance Use Disorder on Treatment Retention of Adult-Attention-Deficit/Hyperactive Disorder Patients. A 5-Year Follow-Up Study - Pallucchini, Alessandro (J Clin Med, 2021)
Attention-Deficit/Hyperactivity Disorder (ADHD) is the most widespread neurodevelopmental disorder, and it still persists into adulthood in 2–6% of the population. Psychiatric comorbidities are very common in adult ADHD (A-ADHD) patients; in particular, Substance Use Disorder (SUD) is found in 40% of these patients. Co-occurrence of ADHD and SUD is described as detrimental to clinical outcome by many authors, while only a few studies describe good clinical results in A-ADHD-SUD patients when they were treated for ADHD, both for the efficacy and the compliance of patients. In this study we tested to determine whether SUD can influence the treatment outcome of A-ADHD patients by correlating lifetime, past and current substance use in A-ADHD patients with their outcome (retention rate) during a 5-year follow-up of patients treated with stimulant and non-stimulant medications, using Kaplan–Meier survival analysis with overall and pairwise comparison. The association between demographic, symptomatological and clinical aspects with retention in treatment, adjusting for potential confounding factors, was summarized using Cox regression. After 5 years of observation, the cumulative treatment retention was 49.0%, 64.3% and 41.8% for A-ADHD patients without lifetime SUD (NSUD/A-ADHD), A-ADHD with past SUD (PSUD/A-ADHD) and A-ADHD with current SUD (CSUD/A-ADHD), respectively. Overall comparisons were not significant (Wilcoxon Rank-Sum (statistical) Test = 1.48; df = 2; p = 0.477). The lack of differences was confirmed by a Cox regression demonstrating that the ADHD diagnosis according to DIVA, gender, education, civil status, presence of psychiatric comorbidity, and psychiatric and ADHD familiarity; severity of symptomatological scales as evaluated by WHODAS, BPRS, BARRAT, DERS, HSRS, and ASRS did not influence treatment drop-out (χ2 22.30; df = 20 p = 0.324). Our A-ADHD-SUD patients have the same treatment retention rate as A-ADHD patients without SUD, so it seems that substance use comorbidity does not influence this clinical parameter.